2021
DOI: 10.1016/j.sjbs.2021.01.062
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of maslinic acid and gallic acid compounds as xanthine oxidase inhibitors in isoprenaline administered myocardial necrotic rats

Abstract: Objective This research designed to analyze the in vivo and in silico ameliorative action of maslinic acid (MA) and gallic acid (GA) on reactive oxygen species generating enzyme xanthine oxidase (XO) in isoprenaline or isoproterenol (ISO) induced myocardial infarcted rats. Methods Albino Wistar rats were categorized into four groups with eight rats in each group. A dose of 15 mg/kg of MA and GA were pretreated to eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Abnormal uric acid metabolism may cause kidney disease, gout, and hyperuricemia. Reducing the production of uric acid by inhibiting XOD activity was an important way to treat uric acid disorder ( 27 ), which had been studied in various materials, including longan seed extract, baicalein, and gallic acid ( 28 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal uric acid metabolism may cause kidney disease, gout, and hyperuricemia. Reducing the production of uric acid by inhibiting XOD activity was an important way to treat uric acid disorder ( 27 ), which had been studied in various materials, including longan seed extract, baicalein, and gallic acid ( 28 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Corosolic acid plays a cardioprotective role against dox-induced cardiotoxicity by restoring autophagic flux and improving mitochondrial function ( Che et al, 2021 ). Maslinic acid ameliorates isoprenaline-induced myocardial necrosis by inhibiting the free radical generating enzyme XO ( Shaik et al, 2021 ). All these findings suggest that terpenoids may exert protective effects in the heart and brain and may be the main medicinal substances of ST.…”
Section: Phytochemical Constituentsmentioning
confidence: 99%
“…erefore, it is necessary to develop new drugs for the chemotherapy treatment of patients with malignant glioma. Maslinic acid is a triterpenoid which was the natural compound widely distributed in medicinal plants [5]. Recent studies have shown that maslinic acid has strong anticancer activity.…”
Section: Introductionmentioning
confidence: 99%
“…Maslinic acid is a triterpenoid which was the natural compound widely distributed in medicinal plants [ 5 ]. Recent studies have shown that maslinic acid has strong anticancer activity.…”
Section: Introductionmentioning
confidence: 99%